Proportional Fair Secondary Receiver Selection Algorithm for Full-duplex WLAN - Kim, Jin Ki; Kim, Yoohwan; Jo, Ju Yeon; Kim, Jae Hyun (International Conference on ICT Convergence, 2020)
Full-duplex (FD) communication supports simultaneous transmission and reception on the same frequency band. It can improve throughput, but it has more interference than half-duplex (HD) communication. Thus, FD communication is possible only when an appropriate secondary receiver (SR) is selected. In this paper, we propose the proportional fair SR selection algorithm. The proposed algorithm takes into account both throughput and fairness by using two weighting factors. The secondary transmitter (ST) selects the SR considering both the weighting factors proportionally. Through extensive simulations, we evaluate the throughput and fairness of our proposed algorithm.
Keywords: Communication support; Extensive simulations; Half-duplex; Proportional fair; Receiver selections; Selection algorithm; Simultaneous transmission; Weighting factors; Full duplex; Proportional fair; SR selection algorithm; WLAN